QRIS Dan Fenomena Cashless Society: Efisiensi Pembayaran Digital Terhadap Perspektif Gen Z - Luthfia Sabrina; Nurul Inayah; Muhammad Syahbudi (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the efficiency level of the QRIS (Quick Response Code Indonesian Standard) digital payment system from the perspective of Generation Z in Medan. The four main indicators measured were transaction speed, ease of use, transaction costs, and system convenience and reliability. This study used a descriptive quantitative approach with 100 active QRIS user respondents. The analysis results showed that QRIS had an overall efficiency level of 79.85%, categorized as "Moderate" according to Tenriajeng's (2003) classification. Transaction speed (83.4%) and ease of use (83.6%) were the most efficient aspects, while transaction costs and system convenience and reliability (76.2%) still need improvement. Theoretically, these findings reinforce the relevance of the Technology Acceptance Model (TAM) and the Bank for International Settlements' concept of payment system efficiency, which emphasizes that perceptions of speed, convenience, and reliability are key factors in the acceptance of digital financial technology. In practice, QRIS has played a significant role in accelerating the transformation toward a cashless society, although improvements in system stability, digital infrastructure, and customer service are still needed to achieve optimal efficiency and strengthen national financial inclusion.